Delamination assessment via acoustic wave propagation and an optical sensor network - Ihsan Naiman, Ibrahim; Mohd Hafizi, Zohari; Mohd Fadhlan, Mohd Yusof; Gigih, Priyandoko (Semarak Ilmu Publishing, 2026)
The preservation of the integrity of composite structures necessitates the monitoring of their structural health. A considerable body of research has been dedicated to investigating the use of traditional electrical sensors for the purpose of collecting acoustic waves in order to detect delamination. In contrast, electrical sensors possess several limitations. This research endeavors to evaluate delamination by employing an optical sensor network that relies on a fiber Bragg grating (FBG) sensor. In the experiment, composite plates were fabricated with varying sizes of delamination. The composite specimen has been equipped with a sensor network consisting of four Fiber Bragg Gratings (FBGs) placed linearly. This network enables the detection of acoustic wave propagation resulting from an impact in the middle of the composite plate. Upon analysis of the acoustic waves, it is seen that the average time delay for various delamination circumstances is 68.2% for a delamination size of 10 cm x 4 cm and 116.7% for a delamination size of 10 cm x 6 cm. The findings of the study also demonstrate that the reduction in wave speed is 40.54% and 53.85% for delamination sizes of 10 cm x 4 cm and 10 cm x 6 cm, respectively. The results indicate that the utilization of a network of Fiber Bragg Grating (FBG) sensors for the purpose of delamination detection in plate-like composite structures holds promise in the field of health monitoring.